Awareness on Kayakalp among health care workers in a tertiary care hospital, Imphal - Debbarma, Bikash; L., Janani; Christina, Soubam; Goutam, Soram; Akoijam, Brogen Singh (International Journal Of Community Medicine And Public Health, 2021)
Background: Kayakalp launched on May 15, 2015 by Government of India, is an initiative to improve cleanliness, hygiene and sanitation of public health facilities by awarding prizes. Awareness among HCWs of an institute can play a vital role in proper implementation of Kayakalp scheme. The study was aimed to assess the knowledge regarding Kayakalp among health care workers. Methods: A cross sectional study was conducted in a tertiary care hospital, Imphal. The study was conducted from September to October, 2019 among key health care workers. Data was collected using an interview schedule. Data were entered in IBM SPSS 21.0 and descriptive statistics were used. Results: Out of 103 participants, majority (64.2%) were nurses, 18.4% were doctors, and 17.4% were laboratory technicians and others. Majority participants (82%) were female and 56% of the participants had been oriented on hospital cleanliness in the past. Majority (91%) of the participants lacked awareness about Kayakalp and its guidelines. Conclusions: In spite of orientation, awareness about Kayakalp among health care workers were found to be inadequate. Periodic training or re-orientation among health care workers is recommended.